Telaah Kritis TFA WTO (World Trade Organization): Analisis terhadap Implementasi Kebijakan Perdagangan Internasional di Indonesia - Deden Rafi Syafiq Rabbani (Jurnal Hukum Lex Generalis, 2021)
The WTO Trade Facilitation Agreement (TFA) is a significant step forward for the international trade regime, representing a new hope for WTO relevance. TFA is the first multilateral agreement since the establishment of the WTO and includes new measures to help developing countries build capacity, as well as considering regulatory issues from WTO members. TFA needs to be interpreted appropriately, a combination of capacity building measures, to be the focus of technology improvement and policy applications, including the policies of each country needed to conduct foreign trade traffic control. TFA is assessed to reduce cross-border trade costs and increase trade for developing countries and allow WTO members to better control trade flows, through a combination of procedural downsizing and regulatory discretion. Through the qualitative normative analysis method, this paper examines legal theories and principles and rules related to international trade law. The author analyzes problems related to the course of trade facilitation agreements within the WTO framework as well as with its implementation in Indonesia. Thus, it is concluded that: First, the implementation of international trade policy in Indonesia based on the presence of TFA, has an important and significant impact on international trade traffic, especially concerning WTO members including Indonesia. Second, the normative regulation of TFA in Indonesia has been regulated in several legal products both laws and presidential regulations, so that the implementation of the presence of TFA affects the control of foreign trade policy and import exports.